RESPONSE OF EARLY RAINY SEASON GRAZING YANKASA RAMS SUPPLEMENTED WITH GRADED LEVELS OF UREA AND/OR COTTON SEED CAKE - Dumbari, M. K.; Abubakar, M.; Kalla, D. J. U.; Abdullahi, H. J. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study was conducted to investigate the response of twentyearly rainy season grazing Yankasa rams supplemented with dietary levels of cotton seed cake and urea. The supplementation was done to augment an unbalanced energy-to-protein ratio, with a relative excess of energy that exits in the tropical grasses under grazing during the rainy season. The treatment consisted of five experimental supplement of 16% CP each, formulated using maize offal, groundnut haulms, rice bran, bone meal, salt and graded levels of cotton seed cake (16.00, 12.00, 8.00, 4.00, and 0.00%) and urea (0.00, 0.50, 1.00, 1.50 and 2.00%) and laid out in a Completely Randomized Design (CRD). Daily supplementation of 400 g quantity was done twice (200 g), in the morning (07:00 hours) and afternoon (15:00 hours). Animals were taken out for grazing after each supplementation. The dry matter and nutrient intake, digestibility, growth performance and haemato-biochemical indices of grazing Yankasa rams were determined. Average daily feed intake of animals fed supplement 1 (392.47 g/day) was statistically (P<0.05) superior to only supplement 5 (282.28 g/day). Daily weight gains of animals fed supplement 1 (75.33 g) similar to those fed on supplement 2, 3 and 4 but was statistically (P<0.05) higher than those fed on supplement 5. Dry matter digestibility of diet 5 (32.65%) was statistically (P<0.05) lower than diet 1, 2, 3 and 4. Supplement 5 recorded the highest feed cost per kg gain (N380.38), whereas supplements 4 recorded the least (N286.66). Based on the result of these findings, supplement 4 can be recommended for early rainy season grazing Yankasa rams.